Non-Small-Cell Lung Cancer Clinicopathologic Features and Survival Outcomes in Asian Pacific Islanders Residing in the United States: A SEER Analysis. (15th January 2015) - Hamid, Muhammad Saad; Shameem, Raji; Gafoor, Khalid; George, Jason; Mina, Bushra; Sullivan, Kevin
Abstract : Background . The objective of our study was to ascertain racial/ethnic disparities in Asian/Pacific Islanders (API) for non-small-cell lung cancer (NSCLC) clinicopathologic features and survival outcomes based on various tumor characteristics and treatment modalities. Method . SEER database identified invasive NSCLC cases from 2004 to 2010. Variables included American Joint Committee on Cancer (AJCC) stage 7, tumor grade, tumor size, histology, age, marital status, radiation, surgery, and reason for no surgery. The Kruskall-Wallis test and theZ test were used to examine differences between races/ethnicities and the referent, non-Hispanic white (NHW). Multivariate Cox proportional analyses were used to establish the weight of the prognostic significance contributing to disease-specific survival (DSS) in each AJCC stage. Result . Improved DSS was seen in API across stage I (HR: 0.78), stage II (HR: 0.79), and stage IV (HR: 0.86), respectively, compared to the referent NHW (P < 0.01 ). Prognosis was improved by being married, being female gender, AIS histology, and birth outside the US (P < 0.01 ). Conclusion . We have demonstrated improved survival among API in early stage and stage IV NSCLC. Further research is necessary to clarify the role of lifestyle and tumor biology for these differences.